Optimal strategy for delirium detection in older patients admitted to intensive care unit after non-cardiac surgery - Wang, Kun; Su, Xian; Ma, Jia-Hui; Wang, Dong-Xin (Frontiers in Surgery, 2023)
Background: Delirium detection is challenging due to the fluctuating nature and frequent hypoactive presentation. This study aimed to determine an optimal strategy that detects delirium with higher sensitivity but lower effort in older patients admitted to the intensive care unit (ICU) after surgery. Methods: This was a secondary analysis of the database from a randomized trial. Seven hundred older patients (aged ≥65 years) who were admitted to the ICU after elective noncardiac surgery were enrolled. Delirium was assessed with the Confusion Assessment Method for the ICU (CAM-ICU) twice daily during the first 7 days postoperatively. The sensitivity of different strategies in detecting delirium were analyzed and compared. Results: Of all enrolled patients, 111 (15.9%; 95% CI: 13.3% to 18.8%) developed at least one episode of delirium during the first 7 postoperative days. Among patients who developed delirium, 60.4% (67/111) had their first delirium onset on postoperative day 1, 84.7% (94/111) by the end of day 2, 91.9% (102/111) by the end of day 3, and 99.1% (110/111) by the end of day 4. Compared with delirium assessment twice daily for 7 days, twice-daily measurements for 4 days detected 99% (95% CI: 94% to 100%) of delirium patients with 57% efforts; twice-daily assessment for 3 days detected 92% (95% CI: 85% to 96%) of delirium patients with only 43% efforts. Conclusions: For older patients admitted to the ICU after elective noncardiac surgery, it is reasonable to detect delirium with the CAM-ICU twice daily for no more than 5 days, and if the personnel and funds are insufficient, 4 days could be sufficient.